Effect of lesion age, humidity, and fungicide application on sporulation of Alternaria alternata, the cause of brown spot of tangerine - Reis, R. F.; de Goes, A.; Mondal, S. N.; Shilts, T.; Brentu, F. C.; Timmer, L. W. (Amer Phytopathological Soc, 2006)
Alternaria brown spot, caused by Alternaria alternata, causes yield losses and fruit blemishes on many tangerines and their hybrids in most citrus areas of the world where susceptible cultivars are grown. Although the conditions affecting infection and disease severity are known, little information is available on inoculum production on infected tissue. We found that sporulation on leaves began about 10 days after symptoms developed, was abundant from 20 to 40 days, and declined thereafter. Conidial production was far greater on leaf than on fruit or twig lesions. Spore production per unit area of leaf lesion was greater on the more susceptible hybrids, Minneola and Orlando tangelos, than on the less susceptible Murcott tangor. At 74% relative humidity, conidial production on leaf lesions was low, but it was abundant at 85, 92.5, 96, and 100%. Application of Q(o)I or copper fungicides, but not ferbam, suppressed sporulation on leaf lesions for about 14 to 21 days after application. Additional applications did not appear to be more effective than a single spray in reducing inoculum production.